Reliability and Validity of the Persian Version of the Fatigue Severity Scale in Idiopathic Parkinson’s Disease Patients - Seyed-Mohammad Fereshtehnejad; Hasti Hadizadeh; Farzaneh Farhadi; Gholam Ali Shahidi; Ahmad Delbari; Johan Lökk (Parkinson's Disease)
As one of the most frequent symptoms, measurement of fatigue is an issue of interest in Parkinson’s disease (PD). The fatigue severity scale (FSS) is one of the recommended questionnaires for this purpose. The aim of our study was to evaluate psychometric properties of the Persian version of the FSS (FSS-Per) to assess fatigue in PD patients. Ninety nondemented idiopathic Parkinson’s disease (IPD) patients were consecutively recruited from an outpatient referral movement disorder clinic. In addition to the disease severity scales, the FSS-Per was used for fatigue measurement. The internal consistency coefficient was larger than 0.8 for all of the items with a total Cronbach’s alpha of 0.96 (95% CI: 0.95–0.97). The FSS-Per score correlated with the UPDRS score (, ) and the “Hoehn and Yahr” (HY) stage (, ). The total score of the FSS-Per significantly discriminated IPD patients with more severe disability (HY stage > 2) versus those with less severe disease (HY stage ) (AUC = 0.81 (95% CI: 0.72–0.90)). The FSS-Per fulfilled a high internal consistency and construct validity to measure the severity of fatigue in Iranian IPD patients. These acceptable psychometric properties were reproducible in subgroups of IPD patients regarding different levels of education, disease severity, sex and age groups.